Clinical and metabolic consequences of two regimens of total parenteral nutrition in the newborn. Issue 3 (March 1983) - Whitfield, M F; Spitz, L; Milner, R D G
Abstract : The clinical and metabolic effects of two regimens of total parenteral nutrition delivering the same amino-acid (2·8 g/kig per 24 h), fat (4·8 g/kg per 24 h), and glucose (12 g/kg per 24 h) load over 24 hours were studied. The regimens differed in the distribution of the infusate during the 24-hour period. With the continuous regimen (7 infants) all nutrients were infused together at a constant rate, whereas with the sequential regimen (9 infants) the daily doses of Vamin/glucose and Intralipid were infused together, followed by the glucose dose. The infants studied had a mean birthweight of 2·8 kg and mean gestational age of 37·9 weeks. Blood levels of glucose, lactate, pyruvate, 3-hydroxybutyrate, acetoacetate, alanine, glycerol, and insulin were measured longitudinally from day 1 to day 21 of total parenteral nutrition. The 7 infants who received the continuous regimen had blood metabolite levels comparable with those of infants fed enterally, with minor fluctuations. Insulin levels were higher than in enterally-fed infants. The 9 infants who received the sequential regimen had wide fluctuations in alanine, glycerol, insulin, 3-hydroxybutyrate, and acetoacetate levels with high peak levels of ketones at the end of the Vamin/glucose and Intralipid infusion, falling to low levels at the end of the 24-hour cycle. There was a gradual reduction in the peak ketone levels from day 6-8 to day 18-21. Clinically unsuspected hypoglycaemia occurred on 6 occasions in each group of infants. There was no significant difference in the incidence of jaundice or infection between the two groups, and the weight velocity during total parenteral nutrition was similar. Wide fluctuations in the infusion rates of individual substrates should be avoided during total parenteral nutrition in the newborn.